Christianity and 'the world': secularization narratives through the lens of English poetry A.D. 800 to the present. - Martin, David (The The Lutterworth Press, 2021)
David Martin was one of the world's leading commentators on secularization theory. He was also a committed and lifelong reader of English poetry. The present book develops Martin's argument against simplistic secularization narratives with reference to the history of poetry, a topic with which few social theorists have been concerned. Martin shows the enduring but ever-changing centrality of Christian thought and practice, in its many different forms, to English poetry. Always mindful that the most important aspects of poetry's history can be captured only by attending to the minutest particulars of individual poems and poets, Martin's study sheds unexpected light on a wide range of English poets, from Spenser and Shakespeare to T.S. Eliot and Geoffrey Hill. The result is a study at once informed by an authoritative sociological perspective on secularization and richly colored by the singular intensity of Martin's own reading life.